Nutrient return through decomposing Coriaria nepalensis litter in degraded hills of Kumaun Himalaya, India - Awasthi, Pankaj; Bargali, Kiran; Bargali, Surendra Singh; Khatri, Kavita (Frontiers in Forests and Global Change, 2022)
Coriaria nepalensis, a nitrogen-fixing actinorhizal shrub, is a prominent and successful colonizer of bare rocks and landslide affected degraded lands. Field experiments were conducted to determine the differences in biomass decomposition and nutrient release pattern of different plant parts of C. nepalensis using litter bag technique. Results showed that the leaves decomposed completely within 6 months while only 46.55% of the lateral roots were decomposed with slowest decomposition rate of 0.14% day–1. The decomposition rate was in the order: Leaves > Reproductive parts > Twigs (< 5 mm) > Twigs (> 5 mm) > Bark > Fine roots > Lateral roots. The decay rate coefficient was highest (0.003–0.014) for leaves and lowest (0.001–0.002) for lateral roots. During the decomposition cycle (364 days), overall increase was reported in nitrogen and phosphorus concentration, while potassium concentration decreased continuously in residual litters. The nutrient mobility was in the order: K > P > N. Climatic factors like temperature, relative humidity and rainfall significantly affected the decomposition process and among these factors, rainfall pattern emerged as a most effective environmental driver. Thus, taking into account initial nutrient content, nutrient release and decay rates, the leaves and reproductive parts of C. nepalensis proved to be more important as nutrient source than other components.